Reduced Emotional Awareness and Distress Concealment: A Pathway to Loneliness for Young Men Seeking Mental Health Care - Kealy, David; Seidler, Zac E.; Rice, Simon M.; Cox, Daniel W.; Oliffe, John L.; Ogrodniczuk, John S.; Kim, Dan (Frontiers in Psychology, 2021)
Background: Loneliness, the painful affective state that reflects perceived deficits in social relationships, is a significant health issue requiring further understanding. Individual differences in awareness and disclosure of emotional concerns may contribute to loneliness, and may do so diversely according to gender and age. The present study examined a hypothesized mediation pathway from emotional awareness abilities to loneliness through distress concealment, with moderation by gender and age, in a sample of adults attending outpatient mental health services. Methods: In a cross-sectional study design, 244 patients attending Canadian community mental health clinics completed study assessments at the commencement of care. Conditional process modelling examined interactions between gender and age and both emotional awareness and distress concealment in mediation models predicting loneliness. Results: A significant three-way interaction between gender, age, and distress concealment was observed, along with significant conditional moderated mediation. The indirect effect of emotional awareness on loneliness through the mediating effect of distress concealment was significant for young- and mid-adulthood men, but not for women or older men. Limitations: The study was limited by exclusive use of self-report assessment, and cross-sectional design precluding representation of causal sequencing over time Conclusions: Findings suggest the pathway to loneliness from reduced emotional awareness through distress concealment to be particularly salient for younger men. Thus, intervention targeting restricted awareness and disclosure of emotional concerns should be considered in helping young men to address the pain of loneliness.